2016
DOI: 10.1007/s11356-016-6414-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition and ecological features of phototrophic biofilms proliferating in the Moidons Caves (France): investigation at the single-cell level

Abstract: The authors investigated the microbial composition of phototrophic biofilms proliferating in a show cave using flow cytometry for the first time in such a context. Results are based on several biofilms sampled in the Moidons Caves (France) and concern both heterotrophic prokaryotes and autotrophic microorganisms. Heterotrophic microorganisms with low nucleic acid content were dominant in biofilms, as can be expected from the oligotrophic conditions prevailing within the cave. Analysis of the biofilm autotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In the Azé cave, the bio lm communities gathered several phototrophic phyla such as the well-known Chlorophyta, Cyanobacteria, Bacillariophyta and Streptophyta [4]. These phyla are frequently described by authors studying the cave microorganism proliferation [17,52,53,54,55]. However, the community distribution and abundance obtained in this study are not comparable to those previously published by other authors.…”
Section: Communities Change Depending Environmental Factorsmentioning
confidence: 57%
“…In the Azé cave, the bio lm communities gathered several phototrophic phyla such as the well-known Chlorophyta, Cyanobacteria, Bacillariophyta and Streptophyta [4]. These phyla are frequently described by authors studying the cave microorganism proliferation [17,52,53,54,55]. However, the community distribution and abundance obtained in this study are not comparable to those previously published by other authors.…”
Section: Communities Change Depending Environmental Factorsmentioning
confidence: 57%
“…However, in this review we focus mainly on life conditions and ecological zones inside karst caves formed on land in carbonate rock (Figure 1) and the microorganisms inhabiting those. Photosynthesizing lichens and algae were reported to live on the cave walls in the cave entrance zone [17,18]. This most external of the cave zones is also most likely to be influenced by visitors from outside: animals and humans [6,15,17].…”
Section: Cave As a Specific Habitatmentioning
confidence: 99%
“…Microbiological analysis of lampenflora biofilm samples revealed that in some cases it consisted of species already present in the cave: the spores and cysts of microorganisms, that were able to enter the vegetative state due to introduction of artificial light [33]. However, the composition of lampenflora differed from natural microorganisms present in the caves with Chlorella and Trohiscia being the dominant genera [18,35,39,49]. These differences in composition are thought to be caused by different growth conditions than those that exist for naturally occurring phototrophs in caves (i.e., the same wavelength and light intensity all year).…”
Section: Photosynthesis and Lampenfloramentioning
confidence: 99%
“…The most significant cited parameters affecting microbial colonisation are physical factors, mainly humidity, temperature, light intensity, and the composition of air pollutants, as well as the chemical nature, mechanical strength, solubility and porosity of the substratum [7],[8]. In general, microbial colonisation is initiated by a wide variety of phototrophic microorganisms, mostly cyanobacteria and algae [9][11]. The colonisation of stone monuments by light-dependent phototrophic types, including cyanobacteria, algae and lichens, allows organic matter in the form of dead cells and trapped debris to be accumulated, enabling heterotrophic or chemoorganotrophic fungi and bacteria to grow on the surface of the stone [12].…”
Section: Introductionmentioning
confidence: 99%